1980
DOI: 10.1093/jn/110.12.2444
|View full text |Cite
|
Sign up to set email alerts
|

Threonine Imbalance, Deficiency and Neurologic Dysfunction in the Kitten

Abstract: The effect of feeding threonine-imbalanced and threonine-deficient purified diets (containing L-amino acids as the only source of dietary nitrogen on food intake, weight gain and blood plasma amino acid pattern has been examined in growing kittens. The imbalance was created by adding 17.5% of amino acid mixture lacking threonine to a low amino acid basal diet comtaining 17.5% amino acid mixture including 0.4% threonine. A depression in food intake and weight gain occurred while feeding the imbalanced diet whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Treatment for gastroenteritis included a prescription diet with a stated crude protein content that was lower than the diet of supplemented minced whole chicken (analyzed by our laboratory) (38.5 vs. 56.94%, respectively), such that the amino acid content of the prescription diet could also be expected to be low, in association with the lower protein content. As observed in this study, no osseous abnormalities were reported in kittens, despite lameness associated with conformational abnormalities of the CV joint [Titchenal et al, 1980] and remission of symptoms in kittens was linked to feeding a diet with adequate levels of all essential amino acids [NRC, 2006;Owen, 1975]. Additionally, in cheetahs reported in this study and elsewhere [Allan et al, 2008], rectification of CV was also associated with a reduction in calcium and vitamin D 3 supplementation to approximately 1% calcium (on a dry matter basis), as well as a more balanced Ca:P ratio of 1-1.5:1.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Treatment for gastroenteritis included a prescription diet with a stated crude protein content that was lower than the diet of supplemented minced whole chicken (analyzed by our laboratory) (38.5 vs. 56.94%, respectively), such that the amino acid content of the prescription diet could also be expected to be low, in association with the lower protein content. As observed in this study, no osseous abnormalities were reported in kittens, despite lameness associated with conformational abnormalities of the CV joint [Titchenal et al, 1980] and remission of symptoms in kittens was linked to feeding a diet with adequate levels of all essential amino acids [NRC, 2006;Owen, 1975]. Additionally, in cheetahs reported in this study and elsewhere [Allan et al, 2008], rectification of CV was also associated with a reduction in calcium and vitamin D 3 supplementation to approximately 1% calcium (on a dry matter basis), as well as a more balanced Ca:P ratio of 1-1.5:1.…”
Section: Discussionsupporting
confidence: 53%
“…reduction in growth rate may in turn have played a role in the observed CV as abnormal flexion of the corono-pedal joints in horses, as well as CV, have previously been associated with a lack of exercise and depressed growth in domestic kittens [Owen, 1975;Titchenal et al, 1980]. The lack of osseous involvement detected by radiography would further support this option.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It has been widely documented that a reduction in feed intake may be regarded as the primary factor responsible for depressed growth in rats, chickens, kittens and beagle dogs fed diets deficient or limiting in Thr (Titchenal et al 1980;Burns & Millner, 1982;Cieslak & Benevenga, 1984;Webel et al 1996). This was also observed in the present study with Atlantic salmon fry as well as in other studies with chum salmon (Oncorhynchus keta; Akiyama et al 1985), rainbow trout (Rodehutscord et al 1995a,b), common carp (Cyprinus carpio; Nose, 1979) and Catla catla (Ravi & Devaraj, 1991).…”
Section: Discussionmentioning
confidence: 99%